Thanatophoric dysplasia type 2: prenatal diagnosis through fetal ultrasound and next-generation sequencing - Wilmar Saldarriaga; Manuel A. Vásquez-Salguero; Viviana López-López (Revista Chilena de Obstetricia y Ginecología)
Thanatophoric dysplasia type 2 (TDII) is a rare and intractable genetic disease caused by de novo mutations in the FGFR3 gene, characterized by severe skeletal anomalies; this condition is lethal during the perinatal period and has a prevalence of 0.21-0.37 cases for every 10,000 births. We report a male fetus with TDII-specific ultrasound findings. Afterward, amniocentesis and cordocentesis were performed, and samples were analyzed using next-generation sequencing (NGS) to perform exome sequencing and Quantitative Fluorescence Polymerase Chain Reaction, k650E (p.Lys659glu, A→G) mutation was found in the FGFR3 gene, reported as pathogenic. Furthermore, the usage of NGS in cell-free fetal DNA, amniotic fluid, and fetal blood is described to establish a skeletal dysplasia diagnosis, accomplishing an early diagnosis to determine the prognosis according to the type of skeletal dysplasia and provide essential information about the pregnancy outcome, either for planning the delivery method or choosing voluntary interruption of pregnancy, in addition to genetic and reproductive counseling.